2020
DOI: 10.30828/real/2020.1.8
|View full text |Cite
|
Sign up to set email alerts
|

The Struggle of Lebanese Teacher Unions in a Neoliberal Period

Abstract: Article InfoTeacher unions worldwide are being criticized for disregarding their responsibility as professionals towards education and students. Critics have claimed that teacher unions tend to protect incompetent teachers, place their own needs and interests above their students, and continuously demand for financial increases even when there is more urgency to elevate teacher professionalism and improve teacher quality. This statement does not take into consideration the political, social and economic aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Mausethagen and Granlund's (2012) study concluded that unions could not take an active role in teacher specialization. In their study, Ghosn and Akkary (2020) investigated the problems experienced by teachers' unions and revealed that the social justice role of the unions is limited, and they cannot take an active role. Wagner and Elder (2021) examined the relationship between teachers' unions' collective bargaining contributions and pension systems in their research and concluded that there is a positive relationship between them.…”
Section: Introductionmentioning
confidence: 99%
“…Mausethagen and Granlund's (2012) study concluded that unions could not take an active role in teacher specialization. In their study, Ghosn and Akkary (2020) investigated the problems experienced by teachers' unions and revealed that the social justice role of the unions is limited, and they cannot take an active role. Wagner and Elder (2021) examined the relationship between teachers' unions' collective bargaining contributions and pension systems in their research and concluded that there is a positive relationship between them.…”
Section: Introductionmentioning
confidence: 99%
“…Also, educational unions are criticized for disregarding their E-ISSN 2721-706X responsibility as professionals toward educations and students. For instance, critics of teacher unions claim that teacher unions tend to protect incompetent teachers, place their own needs and interests above their students and continuously demand salary increase even if there is more urgency to elevate teacher professionalism and improve teacher quality (Ghosn and Akkary 2020).…”
Section: Introductionmentioning
confidence: 99%